(untitled) (Docentes 2.0 Journal, 2024)
The post-pandemic advance has induced profound changes in global social dynamics. This work investigates the impact of emotional intelligence on the school performance of Peruvian students, given the current situation. The purpose of the study is to comprehensively analyze the influence of emotional intelligence on the academic performance of Peruvian students in the post-pandemic context. They adopt a methodological strategy integrating deductive analysis within the socio-critical paradigm, applying a qualitative perspective, and choosing a transversal descriptive narrative design. Data collection involved an exhaustive literature review, examining Scopus, ProQuest, and SciELO databases. In this process, specific terms were searched: “Emotional intelligence,” “Learning,” and “education,” both in Spanish and English, with Boolean operators AND and OR, focusing on works published between 2019 and 2024, with an emphasis on open accessibility. The findings highlighted the need to promote emotional intelligence to improve academic performance. This review demonstrated that teaching emotional skills contributes to relevant learning. Furthermore, managing emotions was key to overcoming educational difficulties during the pandemic. The discussion highlighted the importance of cultivating emotional intelligence and its positive effect on academic performance, considering them essential in post-pandemic times. In summary, the link between emotional intelligence and academic performance is significant, and its promotion is crucial, especially in periods of crisis.